SYSTEMATIC LITERATURE: PROPHETIC PARENTING AND THE MORAL DEVELOPMENT OF ELEMENTARY SCHOOL CHILDREN (INDONESIAN SOCIO-CULTURAL CONTEXT) - Masrurotul Mahmudah; Muh. Ngali Zainal Makmun; Ahwy Oktradiksa (PD PGMI se Indonesia, 2025)
Parenting plays a crucial role in shaping children’s moral development, yet Indonesian parents today face growing challenges, particularly with the increasing dependency of children on gadgets. Many parents rely on smartphones to manage their children’s behavior, which often results in reduced supervision and weakened moral guidance. Research by Layyinatus Syifa et al. indicates that elementary school children who use gadgets for more than two hours a day frequently display irritability, defiance, imitation of inappropriate digital behaviors, and declining discipline. These issues underscore the need for a value-based parenting framework that can effectively address contemporary challenges. In this context, prophetic parenting, rooted in the exemplary nurturing principles of the Prophet Muhammad, offers a model that emphasizes compassion, moral instruction, and character formation. This study examines the relevance of prophetic parenting to the moral development of Indonesian children through a literature review approach. This article conducts an in-depth analysis of the theory of prophetic parenting in shaping a child's morals, drawing from a variety of literature, including books and journals. The research uses a literature study approach with a descriptive-qualitative method. Data was collected from various sources, including published journals, relevant publications, and textual materials. The sources used included books, articles, journals, conference proceedings, and other literature relevant to the research topic. The literature review process in this article follows four steps: (1) preparing relevant literature; (2) compiling a suitable bibliography; (3) managing time and concentrating to minimize bias; and (4) reading carefully, taking notes, and summarizing findings. The researcher then analyzed various findings, including both research results and theories, to narrow down the data and conduct an in-depth analysis consistent with the research objectives. The findings of this study have meaningful implications for both future research and practical parenting. For researchers, the results serve as a valuable reference for further studies on parenting approaches and moral development. For parents, this study offers essential insights by highlighting that prophetic parenting constitutes a fundamental foundation for nurturing and strengthening children's moral development.